Predicting grades from an English language assessment: The importance of peeling the onion. (July 2016) - Bridgeman, Brent; Cho, Yeonsuk; DiPietro, Stephen
Data from 787 international undergraduate students at an urban university in the United States were used to demonstrate the importance of separating a sample into meaningful subgroups in order to demonstrate the ability of an English language assessment to predict the first-year grade point average (GPA). For example, when all students were pooled in a single analysis, the correlation of scores from the Test of English as a Foreign Language (TOEFL) with GPA was .18; in a subsample of engineering students from China, the correlation with GPA was .58, or .77 when corrected for range restriction. Similarly, the corrected correlation of the TOEFL Reading score with GPA for Chinese business students changed dramatically (from .01 to .36) when students with an extreme discrepancy between their receptive (reading/listening) and productive (speaking/writing) scores were trimmed from the sample.